Econometrics study of the impact of financial globalization on economic growth for the period 1995-2015 "The Maghreb countries are a model - meskini, anas; salea, Soumia; sayeh, hamza (Journal of Research in Finance and Accounting, 2021)
This study shows the impact of financial globalization on the economic growth of a sample of the countries of the Maghreb (Algeria, Tunisia and Egypt) during the period 1995-2015. in order to reach the results of this study, we used a econometric model, which is the panel data , after verifying the conditions of its use. The most important results of this study are that the index of the globalization of foreign direct investment and the index of the globalization of international reserves have a positive effect on the increase in gross domestic product.